Registered Bank Holding Company Acquisitions: A Cross-Section Analysis - Moyer, R. Charles; Sussna, Edward (Journal of Financial and Quantitative Analysis, 1973)
A considerable amount of scholarly attention has been focused on the area of banking structure. There have been a number of studies of banking costs under differing market structures, with the goal of defining an economically “optimal” banking structure. A second major body of research has been directed at identifying the impact of given market structures on performance variables. Finally, a third group of analyses has sought an explanation of the process by which a specific structural phenomenon in banking develops and matures. It is within this third broad category of banking structure research that the results reported in this paper may be classified.